The secret wedding [large type] - Beverley, Jo (Thorndike Press, 2009)
In 18th century England, at the age of seventeen, Lt. Christian Hill impulsively defends young Dorcas Froggatt's honor - and finds himself forced into marriage. That doesn't stop him from pursuing his military career abroad, where he swiftly puts his young bride out of his mind - until the past comes back to haunt him. Not long after her traumatic marriage, Dorcas heard that her new husband died in battle. Now she's shocked to learn that he's still alive - and searching for her. (Bestseller)